The wonderful works of God: instruction in the Christian religion according to the Reformed Confession - Bavinck, Herman (Westminster Seminary Press, 2019)
110 years after its original publication, The Wonderful Works of God remains one of the finest single-volume systematic theologies ever written. Adapting the magisterial systematic theology found in his four-volume Reformed Dogmatics, this is perhaps Bavinck's most eminently practical work a single, accessible volume for the college classroom and the family bookshelf. Previously published in America as Our Reasonable Faith, this book has had a deep and lasting influence on the growth and development of Reformed theology. It is the publisher s hope that in its new form, this book continues to astonish readers with the wonderful works of God, and provide a deeper knowledge of their triune God--From Amazon.com